2020
DOI: 10.3390/ijerph17093160
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Balance in Patients with Fibromyalgia Syndrome: Predictors of the Impact of This Disorder and Balance Confidence

Abstract: Patients with fibromyalgia syndrome (FMS) have a nonspecific postural balance disorder and a greater prevalence of falls. Objective: to clarify which aspects of maintaining balance are associated with the impact of the disorder and with balance confidence. Methods: A total of 182 persons with FMS agreed to participate in this study. After re-evaluation, 57 fully met inclusion criteria: age 40–70 years and moderate-severe impact of the illness according to the Fibromyalgia Impact Questionnaire (FIQ). All partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 33 publications
2
34
0
Order By: Relevance
“…Postural control is a term used to describe regulation of the nervous system in order to produce and maintain a controlled, upright posture [10]. Instable postural control is one of the first signs and symptoms of many neurological diseases and cognitive impairments [11,12] and is evident in fibromyalgia, which is a wellestablished CS-related pain syndrome [13,14]. Subjective dizziness, vertigo and unsteadiness are also common symptoms of fibromyalgia [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Postural control is a term used to describe regulation of the nervous system in order to produce and maintain a controlled, upright posture [10]. Instable postural control is one of the first signs and symptoms of many neurological diseases and cognitive impairments [11,12] and is evident in fibromyalgia, which is a wellestablished CS-related pain syndrome [13,14]. Subjective dizziness, vertigo and unsteadiness are also common symptoms of fibromyalgia [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have found an alteration of postural control in FMS subjects [ 9 , 10 , 11 ]. FMS is also associated with an increased fall prevalence [ 12 ] and a greater awareness of their balance problems [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…This task requires the rapid and dynamic integration of convergent sensory information from somatosensory, vestibular and visual systems, which are needed to maintain the balance [ 13 , 14 ]. The alteration of the balance can be related to poor balance confidence, increasing the risk of falls [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown a correlation between impaired balance and an increased risk of falling and/or a higher frequency of falls in women with FMS with reduced balance compared to healthy subjects [ 16 ]. FMS subjects reported an incidence of falls of 1.75 falls per person each six months [ 15 ]. Furthermore, balance alterations in patients with FMS negatively impact physical function, gait and quality of life [ 15 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation